Carbon nanotube magnetic functional material loaded with Co nanoparticles as well as preparation method and application of carbon nanotube magnetic functional material

By attaching carbon nanotube magnetic functional materials loaded with Co nanoparticles to the screen printing electrode and using magnets to achieve material regeneration, the problems of high cost of existing screen printing electrodes and poor stability of magnetic nanomaterials are solved, and the problem of high cost of existing screen printing electrodes and poor stability of magnetic nanomaterials is achieved. Preparation and efficient detection capabilities of regenerated electrodes.

CN119394734AActive Publication Date: 2025-02-07HUNAN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410252446.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-06
Publication Date
2025-02-07
Estimated Expiration
2044-03-06

AI Technical Summary

Technical Problem

The existing screen-printed electrodes are costly due to their single use and the chemical stability of magnetic nanomaterials is poor, making it difficult to meet the needs of long-term applications.

Method used

By designing a magnetic base, carbon nanotube magnetic functional materials (Co@CNTs) loaded with Co nanoparticles are attached to the surface of the screen printing electrode, and the regeneration and recycling of materials are achieved by using magnets to prepare a renewable magnetic screen printing electrode. .

Benefits of technology

The reproducibility of screen-printed electrodes is realized, reducing the cost of use. At the same time, due to the high specific surface area of ​​Co@CNTs and the excellent electron transfer rate, the detection ability of hydrazine hydrate and tartar yellow is significantly improved, and the detection limit is low. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119394734A_ABST
    Figure CN119394734A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Co nano particle loaded carbon nano tube magnetic functional material (Co (at) CNTs). Due to the synergistic effect of the Co nanoparticles and the carbon tubes, the material shows excellent electrocatalytic property, conductivity and rapid electron transfer ability. A renewable magnetic screen-printed electrode is developed by combining a designed magnetic base and a screen-printed electrode (SPE). In the presence of Co-coated CNTs, the electron transfer kinetics of hydrazine hydrate and tartar yellow on the surface of SPE is greatly improved. The detection linear ranges of the Co (at) CNTs / SPCE on hydrazine hydrate and tartar yellow are 0.1 to 50.0 mM and 0.04 to 30.0 mM, and the detection limits are respectively 50 nM and 12 nM. The Co-coated CNTs are attached to the surface of the SPE under the control of the magnet and are easily separated from the surface of the electrode through the magnet, so that the sensor is simple in structure, renewable and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical analysis, and specifically provides a carbon nanotube magnetic functional material loaded with Co nanoparticles, and a preparation method and application thereof. Background Art

[0002] Magnetic functional nanomaterials have been widely used as catalysts or adsorbents due to their easy operation and simple separation. Under the action of an external magnetic field, their controllable spatial distribution allows them to be used in interface-related fields. And through magnetic separation, magnetic materials can be quickly and effectively recovered and regenerated, which will potentially reduce capital investment. In addition, some nanomaterials with controllable magnetism have been developed through size effects and chemical composition. Metals such as iron, cobalt, and nickel are used as the main source of magnetism due to their high saturation magnetization. However, the chemical stability of pure metal nanoparticles is very poor because their antioxidant capacity is very weak. In order to improve the stability of magnetic nanomaterials and obtain magnetic nanomaterials with specific functions, researchers have adopted a method of combining magnetic elements with other substrates. For example: magnetic nanofibers loaded with iron oxide were synthesized for the manufacture of morphine electrochemical sensors; a magnetic cellulose-chitosan hydrogel and Fe3O4 composite adsorbent was prepared for the removal of heavy metal ions; a separable and recyclable magnetic carbon nanotube was prepared and coated with Ni nanoparticles for Hg 2+ Detection; A magnetic Ni@NCNT was synthesized and used for persulfate activation to remove pollutants. Ni@NCNT still has strong magnetism and stability after acid washing.

[0003] Screen-printed electrode (SPE) is a substitute for traditional electrodes. It generally includes a substrate for printing electrodes, an external insulating layer and electrode leads are printed on the substrate, and three electrodes are printed on the substrate, namely, working electrode (WE), reference electrode (RE) and auxiliary electrode (AE). Each electrode is connected to the corresponding lead to form a classic electrochemical three-electrode system. It has the following characteristics: small size, powerful function, can realize on-site and real-time analysis; multifunctional, customizable, can meet a variety of needs; high repeatability; low cost and maintenance-free. Because it has characteristics and advantages that traditional electrodes cannot replace, it is used in the environment, clinical or agricultural food fields. However, the screen-printed electrodes currently used are disposable electrodes. For some types that use printed gold paste as working electrodes, their use cost is relatively high. Therefore, we combine the advantages of magnetic materials and propose a preparation of a regenerative magnetic screen-printed electrode. By designing a magnetic base, the magnetic functional nanomaterials are controlled to attach to the surface of the screen-printed electrode, and the magnetic functional materials are separated from the electrode surface by a magnet to achieve the purpose of regenerating the electrode surface. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of a carbon nanotube magnetic functional material loaded with Co nanoparticles.

[0005] To achieve the above-mentioned purpose, the technical scheme adopted by the present invention includes: a method for preparing a carbon nanotube magnetic functional material (Co@CNTs) loaded with Co nanoparticles, which comprises fully mixing an appropriate amount of dried and dehydrated cobalt metal salt, starch, and dicyandiamide, transferring the mixture into an alumina crucible after ball milling, heating the mixture in a tubular furnace with programmed temperature increase, performing two-stage temperature-controlled pyrolysis, and collecting a black product after cooling.

[0006] Preferably, the mass ratio of dicyandiamide to starch is 3:1~20:1; the step heating temperature rise rate is 2~4°C·min-1; the two-stage pyrolysis control temperatures are 850-900 K and 1050-1100 K, respectively, and the temperature control time is 2-8 h and 1-4 hours, respectively; the tubular furnace is protected by N2 or Ar gas.

[0007] Preferably, the mass ratio of dicyandiamide to metal Co salt is 2:1 to 20:1.

[0008] Carbon nanotube magnetic functional materials loaded with Co nanoparticles (Co@CNTs) were prepared according to the described method.

[0009] The application of the Co nanoparticle-loaded carbon nanotube magnetic functional material (Co@CNTs) prepared by the method described in the preparation of reproducible magnetic screen-printed electrodes.

[0010] A method for preparing a reproducible magnetic screen-printed electrode comprises the following steps: (1) Design the magnetic base: including the base, hard electrode slot, magnet of appropriate size, electrode horizontal platform, and fixing screws; (2) Insert the screen-printed electrode into a magnetic base, activate it, and disperse the Co@CNTs in a suitable solvent. Add the Co@CNTs dispersion dropwise onto the surface of the working electrode, then use filter paper to absorb the solvent and wash it. To regenerate the electrode surface, remove the electrode from the magnetic base and use a magnet to remove the Co@CNTs.

[0011] Preferably, the materials used for the parts in step (1) are all insulating materials, the size of the basic base ranges from 6 to 15 cm in length and 2 to 6 cm in width, and the magnet is fixed on the base.

[0012] Preferably, in step (1), the size of the hard slot matches the size of the screen-printed electrode; the hard electrode slot fixes the screen-printed electrode, and the screw fixes the electrode slot; the size of the magnet is consistent with the size of the working electrode of the screen-printed electrode, and the relative horizontal positions overlap; the electrode horizontal platform stabilizes the electrode adapter.

[0013] Preferably, the mass concentration of the Co@CNTs dispersion in step (2) is 0.2-4.0 mg / mL; the method for activating the screen-printed electrode is: in 0.1 mol / L H2SO4, cyclic voltammetry is used to scan 4-10 times in the range of -0.6 V to +1.2 V at a certain scan rate, and then washed and dried under N2; According to the method, a reproducible magnetic screen-printed electrode is prepared using magnetic functional materials and its application.

[0014] In the present invention, carbon nanotubes loaded with Co nanoparticles are prepared by high-temperature pyrolysis, and can be modified on the surface of screen-printed electrodes by drop coating to obtain regenerative magnetic screen-printed electrodes. The oxidation peak current conducted by the electrode has a linear correlation with the content of hydrazine hydrate and tartrazine. The carbon nanotube magnetic functional material loaded with Co nanoparticles (Co@CNTs) has a large specific surface area and excellent electron transfer rate. Since it is loaded with Co metal nanoparticles, the electrocatalytic performance is greatly improved through the synergistic effect with carbon tubes. The regenerative magnetic screen-printed electrode prepared by the material can quickly determine the content of hydrazine hydrate and tartrazine, and the detection limit is low; the magnetic functional nanomaterial can be controlled to attach to the surface of the screen-printed electrode by a magnet, and can also be completely separated from the electrode surface by a magnet, so as to achieve the purpose of regenerating the electrode and reducing the cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The scanning electron microscope image (A) and the transmission electron microscope image (B) of the carbon nanotube magnetic functional material loaded with Co nanoparticles prepared in Example 1.

[0016] Figure 2 Schematic diagram of the dispersion of the carbon nanotube magnetic functional material loaded with Co nanoparticles prepared in Example 1 in the presence or absence of a magnetic field.

[0017] Figure 3 Schematic diagram of the magnetic base designed for Example 1 being inserted into the screen-printed electrodes.

[0018] Figure 4 Cyclic voltammograms of the magnetic screen-printed electrode (Co@CNTs / SPE) prepared in Example 1 and the bare screen-printed electrode (SPE) for the electrocatalytic oxidation of hydrazine hydrate (A) and tartrazine (B). DETAILED DESCRIPTION

[0019] The following are the preparation of the carbon nanotube magnetic functional material loaded with Co nanoparticles of the present invention, the preparation of the reproducible magnetic screen printing and the detection of hydrazine hydrate and tartrazine. The following examples are intended to further illustrate the present invention in detail, but not to limit the present invention. Example

[0020] (1) Preparation of carbon nanotubes loaded with Co nanoparticles: 5.0 g of dicyandiamide, 0.5 g of starch, and 0.4 g of cobalt acetate were dry mixed and ball milled for 24 h. The solid powder was transferred to a tube furnace and heated at 4 °C min under N2 atmosphere. -1 The temperature was raised stepwise to 873 K at a rate of 1.5 °C·min -1 The temperature was raised to 1073 K at a rate of 1.5 ℃ and kept at this temperature for 2 hours, then cooled, fully ground and the black product was collected to obtain the magnetic functional material of carbon nanotubes loaded with Co nanoparticles (Co@CNTs); (2) Design a magnetic base; the basic base is 8 cm long and 4 cm wide; a disk magnet with a diameter of 5 mm and a thickness of 2 mm is installed on the base; a hard screen-printed electrode slot is installed above the magnet and fixed with screws. The inner cavity size of the screen-printed electrode is 1´1.5 cm; the size of the base magnet is consistent with the working electrode size of the screen-printed electrode, and the relative position can overlap; the electrode horizontal platform fixed with screws stabilizes the electrode adapter so that the screen-printed electrode can stably maintain a horizontal direction.

[0021] (3) Construction of a reproducible magnetic screen-printed electrode (Co@CNTs / SPE): First, the printed electrode was inserted into the electrode slot of the designed magnetic base, 0.1 mol / L H2SO4 was added to the electrode surface, and the electrode surface was heated at 50 mV s -1 At the scanning rate, cyclic voltammetry was used to scan 5 cycles in the range of - 0.6 V to + 1.2 V to activate the electrode, then wash it with ethanol and dry the electrode surface under N2; Co@CNTs were dispersed in N, N-dimethylformamide. 6 mL of Co@CNTs dispersion (0.5 mg / mL) was added to the surface of the working electrode, and then the solvent was absorbed with filter paper and washed with water. In order to regenerate the electrode surface, the electrode was removed from the magnetic base and the Co@CNTs on the electrode surface were sucked away with a magnet. After the electrode was activated again, secondary material modification can be performed.

[0022] (4) Electrochemical determination of hydrazine hydrate: The Co@CNTs / SPE constructed in step (3) is used as an electrical signal sensing device, 0.1 mol / L phosphate buffer solution is used as the electrolyte, the pH value is 7.0, and the test method is cyclic voltammetry; the test solution of standard concentration is added to the electrode surface, the oxidation peak current value of hydrazine hydrate at different concentrations is recorded, and a standard curve of current-concentration is drawn. When testing the sample, the measured oxidation peak current value is compared with the standard curve to calculate the hydrazine hydrate content in the sample to be tested.

[0023] (5) Characterization of the magnetic functional material obtained in this example and the performance of the sensor: Figure 1It can be seen that the prepared material has a tubular structure loaded with metal nanoparticles, the particle size of the nanoparticles is about 10-80nm, and the diameter of the nanotubes is about 20-150nm. Figure 2 It shows that the prepared Co@CNTs have good magnetic properties. Figure 3 The designed magnetic base can stably fix the screen-printed electrodes. Figure 4 By comparing with the bare printed electrode (SPE), it was found that the magnetic Co@CNTs / SPE greatly enhanced the oxidation peak of hydrazine hydrate, and its oxidation peak current was 6.7 times that of the former. Example

[0024] (1) The preparation of carbon nanotubes loaded with Co nanoparticles is the same as in Example 1.

[0025] (2) Design a magnetic base; the basic base is 10 cm long and 3 cm wide; a disk magnet with a diameter of 5 mm and a thickness of 4 mm is installed on the base; the electrode slot is glued and fixed above the magnet, and the cavity size in the slot is 1´3 cm; the size of the base magnet is consistent with the size of the working electrode of the screen-printed electrode, and the relative position can overlap; the electrode horizontal platform is glued and fixed to stabilize the electrode adapter, so that the screen-printed electrode can stably maintain a horizontal direction.

[0026] (3) The construction of the reproducible magnetic screen-printed electrode (Co@CNTs / SPE) is the same as in Example 1.

[0027] (4) Electrochemical determination of tartrazine: The Co@CNTs / SPE constructed in step (3) is used as an electrical signal sensing device, 0.1 mol / L phosphate buffer solution is used as the electrolyte, the pH value is 6.5, and the test method is differential pulse voltammetry; a test solution with a standard concentration of tartrazine is added to the electrode surface, the oxidation peak current value of tartrazine at different concentrations is recorded, and a standard curve of current-concentration is drawn. When testing the sample, the measured oxidation peak current value is compared with the standard curve to calculate the content of tartrazine in the sample to be tested.

[0028] (5) Sensing performance of the renewable Co@CNTs / SPE prepared in this example: Figure 4 It can be seen that compared with the bare printed electrode (SPE), the magnetic Co@CNTs / SPE greatly enhanced the oxidation peak of tartrate yellow, and its peak current was 3.9 times that of the former. Example

[0029] (1) Preparation of carbon nanotubes loaded with Co nanoparticles: 3.0 g of dicyandiamide, 0.8 g of starch and 0.5 g of hexaamminecobalt trichloride were dry mixed and ball milled for 15 h. The solid powder was transferred to a tube furnace and heated at 2 °C min under N2 atmosphere. -1The temperature was raised stepwise to 823 K at a rate of 1.5 °C·min -1 The temperature was raised to 1023 K at a rate of 1.5 ℃ and kept at this temperature for 3 hours, then cooled, fully ground and the black product was collected to obtain the magnetic functional material of carbon nanotubes loaded with Co nanoparticles (Co@CNTs); (2) Design the magnetic base in the same way as in Example 1.

[0030] (3) Construction of a reproducible magnetic screen-printed electrode (Co@CNTs / SPE): First, the printed electrode was inserted into the electrode slot of the designed magnetic base, 0.1 mol / L H2SO4 was added to the electrode surface, and the electrode surface was heated at 20 mV s -1 At the scanning rate, cyclic voltammetry was used to scan 8 cycles in the range of - 0.6 V to + 1.2 V to activate the electrode, then rinse with water and dry the electrode surface under N2; Co@CNTs were dispersed in ethanol solvent. 10 mL of Co@CNTs dispersion (3.0 mg / mL) was added to the surface of the working electrode, ethanol was absorbed with filter paper, and washed with water. In order to regenerate the electrode surface, the electrode was removed from the magnetic base and the Co@CNTs on the electrode surface were sucked away with a magnet. After the electrode is activated, secondary material modification can be performed.

[0031] (4) The electrochemical determination of hydrazine hydrate is the same as in Example 2.

Claims

1. A method for preparing a carbon nanotube magnetic functional material (Co@CNTs) loaded with Co nanoparticles, characterized in that: A proper amount of dried and dehydrated cobalt metal salt, starch and dicyandiamide are fully mixed, and after ball milling, the mixture is transferred into an alumina crucible, and programmed temperature is increased in a tube furnace, and two-stage temperature-controlled pyrolysis is performed, and the black product is collected after cooling.

2. The method for preparing the Co nanoparticle-loaded carbon nanotube magnetic functional material (Co@CNTs) according to claim 1, characterized in that: In step (1), the mass ratio of dicyandiamide to starch is 3:1~20:1; the step heating temperature rise rate is 2~4°C·min-1; the double-stage pyrolysis control temperatures are 850-900 K and 1050-1100 K, respectively, and the temperature control time is 2-8 h and 1-4 hours, respectively; the tubular furnace is protected by N2 or Ar gas.

3. The method for preparing the Co nanoparticle-loaded carbon nanotube magnetic functional material (Co@CNTs) according to claim 1, characterized in that: In step (1), the mass ratio of dicyandiamide to metal Co salt is 2:1 to 20:

1.

4. A magnetic functional material of carbon nanotubes loaded with Co nanoparticles (Co@CNTs) prepared according to the method of claim 1.

5. Use of the carbon nanotube magnetic functional material loaded with Co nanoparticles (Co@CNTs) prepared by the method of claim 1 in preparing a renewable magnetic screen-printed electrode.

6. The use according to claim 1, characterized in that: A method for preparing a reproducible magnetic screen-printed electrode comprises the following steps: (1) Design the magnetic base: including the base, hard electrode slot, magnet of appropriate size, electrode horizontal platform, and fixing screws; (2) Insert the screen-printed electrode into a magnetic base, activate it, and disperse the Co@CNTs in a suitable solvent; drip the Co@CNTs dispersion onto the surface of the working electrode, then use filter paper to absorb the solvent and wash it; in order to regenerate the electrode surface, remove the electrode from the magnetic base and use a magnet to absorb the Co@CNTs.

7. The use according to claim 6, characterized in that: The materials used for the parts in step (1) are all insulating materials. The size of the basic base ranges from 6 to 15 cm in length and 2 to 6 cm in width. The magnet is fixed on the base.

8. The use according to claim 6, characterized in that: In step (1), the size of the hard card slot matches the size of the screen-printed electrode; the hard electrode card slot fixes the screen-printed electrode, and the screw fixes the electrode card slot; the size of the magnet is consistent with the working electrode size of the screen-printed electrode, and the relative horizontal positions overlap; the electrode horizontal platform stabilizes the electrode adapter.

9. The use according to claim 6, characterized in that: The mass concentration of the Co@CNTs dispersion in step (2) is 0.2-4.0 mg / mL; the method for activating the screen-printed electrode is: In 0.1 mol / L H2SO4, cyclic voltammetry was used to scan 4 to 10 times in the range of -0.6 V to +1.2 V at a certain scan rate, and then the sample was washed and dried under N2.

10. The use according to claims 5-9, characterized in that Reproducible magnetic screen-printed electrodes prepared using magnetic functional materials and their applications.

Citation Information

Patent Citations

  • Preparation method and application of hollow magnetic Co / carbon nano tube

    CN106964315A

  • Preparation method of ultrafine nitrogen-doped carbon hollow nanotubes and product and application thereof

    CN109534316A